Cleavage of the papillomavirus minor capsid protein, L2, at a furin consensus site is necessary for infection - Richards, Rebecca M. (National Academy of Sciences, 2006)
Papillomaviruses (PV) comprise a large family of nonenveloped DNA viruses that include the oncogenic PV types that are the causative agents of human cervical cancer. As is true of many animal DNA viruses, PV are taken into the cell by endocytosis and must escape from the endosomal compartment to the cytoplasm to initiate infection. Here we show that this step depends on the site-specific enzymatic cleavage of the PV minor virion protein L2 at a consensus furin recognition site. Cleavage by furin, a cell-encoded proprotein convertase, is known to be required for endosome escape by many bacterial toxins. However, to our knowledge, furin has not been previously implicated in the viral entry process. This step is potentially a target for PV inhibition.